Marketing Strategy in Latin American Region for GE Aviation H-series Turboprop Engines - Khlynin, Artem (2019)
The objective of this master thesis is to evaluate the current market position of GE Aviation’s turboprop aircraft engines in the Latin American region. The outcome of this thesis is a decision on the market perspectives and opportunities for the company. The conclusion is based on the analysis of macroeconomic factors of the selected region; aircraft fleet structure, trends and opportunities; analysis of competition; and the results of three interviews conducted with GE Aviation Czech representatives. First, the theoretical part is concentrated on the topics of market and competition analysis. Interview methodology is described at the end of the first part. Second, the analytical part is dedicated to the economic analysis of Latin American markets with an emphasis on key countries and regions. The research is concentrated on the current competition and the Latin American market. Moreover, general trends in the aviation sector are described and analyzed in the perspective of a turboprop aircraft. Interview results with leading sales and business development representatives are provided in the last part of the thesis. The general conclusion on possible market strategy is made based on primary and secondary research results and on the interview results interpretation.